Current Trends in Drug Delivery System of Curcumin and its Therapeutic Applications - Sethiya, Ayushi; Agarwal, Dinesh Kr.; Agarwal, Shikha (Mini Reviews in Medicinal Chemistry, 2020)
Curcumin is a poly phenolic compound extracted from turmeric. Over the past years, it has acquired significant interest among researchers due to its numerous pharmacological activities like anti- cancer, anti-alzheimer, anti-diabetic, anti-bacterial, anti-inflammatory and so on. However, the clinical use of curcumin is still obstructed due to tremendously poor bioavailability, rapid metabolism, lower gastrointestinal absorption, and low permeability through cell that makes its pharmacology thrilling. These issues have led to enormous surge of investigation to develop curcumin nano formulations which can overcome these restrictive causes. The scientists all across the universe are working on designing several drug delivery systems viz. liposomes, micelles, magnetic nano carriers, etc. for curcumin and its composites which not only improve its physiochemical properties but also enhanced its therapeutic applications. The review aims to systematically examine the treasure of information about the medicinal use of curcumin. This article delivers a general idea of the current study piloted to overwhelm the complications with the bioavailability of curcumin which have exhibited an enhanced biological activity than curcumin. This article explains the latest and detailed study of curcumin and its conjugates, its phytochemistry and biological perspectives and also proved curcumin as an efficient drug candidate for the treatment of numerous diseases. Recent advancements and futuristic viewpoints are also deliberated, which shall help researchers and foster commercial translations of improved nanosized curcumin combination for the treatment of various diseases.
Keywords: drug delivery system